Three-dimensional modelling and morphometric analysis of skull of badger (Meles meles) with computed tomography images - Kanmaz, Yesim Aslan; Guzel, Baris Can; Baygeldi, Saime Betuel; Karan, Meryem (Wiley, 2024)
Background: Morphometric measurements help to understand the skull morphology in different animal species, detect skull deformations and figure out their causes. Objectives: The aim of this study is to make a three-dimensional (3D) modelling of the badger skull using computed tomography, to show its anatomical structures and to reveal the morphometric measurement values. Methods: Skull measurements were carried out using a digital calliper at 27 measurement points based on metric measurement points. After the scanned images were stored in Digital Imaging and Communications in Medicine format, they were transferred to MIMICS 20.1 (The Materialize Group) programme and 3D models the skulls were created. The surface area and volume values of the skulls were calculated on these models. Results: The volume and surface area parameters were expressed as mean +/- SE. Four different indices were calculated using osteometric measurements. Statistical analyses were made by determining the mean value and standard deviation of the examined properties and the correlation coefficients among these properties. In the metric measurement points taken as a basis, the longest measurement in the skulls was the total length and its mean value was 124.60 +/- 0.64 mm. The shortest measurement was the breadth dorsal to the external auditory meatus, and its mean value was 6.75 +/- 0.24 mm. Conclusions: Consequently, statistical differences in the craniometric values of badgers' skulls were determined by using CT and 3D modelling software. In addition, it was concluded that the badger skull can be easily distinguished from other carnivore species by carrying out morphometric measurements.
Keywords: computed tomography; Meles meles; morphometric analysis; reconstruction; skull